Updated incidence rates and risk factors of esophageal cancer in Nan'ao Island, a coastal high-risk area in southern China. Issue 1 (21st December 2016) - Tan, Hua-Zhen; Lin, Wen-Jie; Huang, Jin-Qu; Dai, Meng; Fu, Jian-Hua; Huang, Qing-Hua; Chen, Wei-Min; Xu, Yi-Long; Ye, Ting-Ting; Lin, Ze-Ying; Lin, Xiao-Sheng; Cai, Jian-Xiong; et al.
SUMMARY: Esophageal cancer (EC) is one of the most common cancers in China. The purpose of this study was to investigate the updated incidence rates and risk factors of EC in Nan'ao Island, where the EC incidence rate was chronically the highest in southern China. To calculate the annual incidence rate, data on 338 EC cases from Nan'ao Cancer Registry system diagnosed during 2005–2011 were collected. A case-control study was conducted to explore the EC risk factors. One hundred twenty-five alive EC patients diagnosed during 2005–2011 and 250 controls were enrolled into the case-control study. A pre-test questionnaire on demography, dietary factors, drinking water treatment, and behavioral factors was applied to collect information of all participants. The average EC incidence rates during 2005–2011 were 66.09/10 5, 94.62/10 5, 36.83/10 5 for both genders, males and females, respectively, in Nan'ao Island. The EC incidence rate in males was 2.40- to 4.55-fold higher than that in females in the period from 2006 to 2011 ( P  < 0.05). Considering the onset age, males tend to be much younger than females and reached peak incidence rate at a younger age ( P  < 0.05). Drinking water treatment by filter (odds ratio [OR] = 0.28, 95% confidence interval [95% CI] = 0.13–0.58) and fruit consumption (OR = 0.55, 95% CI = 0.32–0.94) reduced the risk for EC. On the contrary, the pickled vegetables consumption (OR = 2.64, 95% CI = 1.46–4.76) and liquor drinking (OR = 2.32, 95% CI = 1.21–4.44) increased the risk for EC. These results may be of importance for future research on EC etiology and prevention strategies.